Identifying strategic entry points for transformative politics towards a degrowth society: how to operationalize the concept of the “imperial mode of living” for empirical research - Timmo Krüger (Innovation: The European Journal of Social Science Research, 2020)
The research on socio-ecological transformation has thus far focused on the necessity and the possible design of a transformed society. What is missing are empirical studies on the potentials and constraints of such a far-reaching transformation. One reason for this is the necessity to develop complex research designs, particularly, the need to capture the micro-level of subjects, on the one hand, as well as the macro-level of societal structures, on the other hand. A concept that systematically links both levels is that of the 'imperial mode of living'. This paper outlines how the concept can be operationalized. First, different components of the concept are analytically distinguished. Second, how the interpretation of enthymemes can be made productive for analyzing the stability of the imperial mode of living is shown. These insights provide essential background information that can be used to identify strategic entry points for transformative politics towards a degrowth society.
Keywords: 710; Degrowth; Enthymemes; Imperial mode of living; Hegemony; Socio-ecological transformation; Sufficiency; Transformative politics